ENSO impacts child undernutrition in the global tropics - Anttila-Hughes, Jesse K.; Jina, Amir S.; McCord, Gordon C. (Nature communications, 2021)
The El Niño Southern Oscillation (ENSO) is a principal component of global climate variability known to influence a host of social and economic outcomes, but its systematic effects on human health remain poorly understood. We estimate ENSO’s association with child nutrition at global scale by combining variation in ENSO intensity from 1986-2018 with children’s height and weight from 186 surveys conducted in 51 teleconnected countries, containing 48% of the world’s under-5 population. Warmer El Niño conditions predict worse child undernutrition in most of the developing world, but better outcomes in the small number of areas where precipitation is positively affected by warmer ENSO. ENSO’s contemporaneous effects on child weight loss are detectable years later as decreases in height. This relationship looks similar at both global and regional scale, and has not appreciably weakened over the last four decades. Results imply that almost 6 million additional children were underweight during the 2015 El Niño compared to a counterfactual of neutral ENSO conditions in 2015. This demonstrates a pathway through which human well-being remains subject to predictable climatic processes. The El Nino Southern Oscillation (ENSO) influences the weather around the world and, therefore, has strong impacts on society. Here, the authors show that ENSO is associated with child nutrition in many countries, with warmer El Niño conditions leading to more child undernutrition in large parts of the developing world.